Evaluating older adult self-care capacity. Issue 2 (March 2019) - Moore, Amy; Merrill, Emily
Abstract : In multiple settings, nurses have opportunities to observe patients' abilities to make decisions and live safely at home. Abstract : In multiple settings, nurses have opportunities to observe patients' abilities to make decisions and live safely at home.